Electrophoretic Haemolymph Protein Profile in Beauveria bassiana Inoculated and Subsequent Treatment of Ethanolic Plant Extracts, Dusting of Plant Powder in Silkworm Bombyx mori L. - A., Chavan J.; B, Gaikwad Y.; P., Bhawane G. (Asian Journal of Biological and Life Sciences, 2013)
The effect of Beauveria bassiana and subsequent treatment of ethanolic plant extracts and dusting of plant powder on concentration of the haemolymph proteins were examined in the larvae of Bombyx mori PM race on the 3rd and 5rd day of 5th instar by SDS-PAGE. The electrophoretic analysis of haemolymph proteins revealed separation of maximum 18 protein bands among which some of them represents the storage proteins. The B. bassiana inoculation causes the decrease in number of protein bands and staining intensity was also low as compared to the control. The treatment of plant extracts orally and dusting of plant powder also shows the decreased protein bands and staining intensity loe but in Curcuma longa and Argemone mexicana trated group shows the similar protein bands when compared with the control group sample.